Integration of the Da'wah of Tawhid in the Economic Activities of Muslim Communities: Challenges and Strategies - Nuradi, Nuradi; Husnul Khatimah; Fathan Qoriba; Adi Wijaya (El-kahfi | Jurnal Ekonomi Islam, 2025)
The integration of monotheism in economic activities will undoubtedly significantly impact the socio-economic well-being of Muslim societies. While a large body of literature discusses the relationship between religion and economics, few studies specifically explore the effective integration of the concept of tawhid into the economic practices of Muslim societies. This research aims to bridge this gap by examining a comprehensive approach to incorporating the principles of tawhid into economic activities. The aim is to create a strong synergy between faith and economic practices in daily life. A systematic analysis of secondary data sources, including journal articles, books, conference reports, and dissertations, identified key themes and practical methods for implementing the values of tawhid in various aspects of business operations, such as financial management, investment decisions, and employee relations. The findings are clear: Integrating tawhid strengthens the spiritual foundation of Muslim societies and contributes to more ethical, transparent, and sustainable business practices. However, implementing the strategy has encountered some challenges that must be addressed with suitable strategies, which are also outlined in this study. This research offers practical recommendations for economic actors and religious leaders, contributing to the growing knowledge of the intersection of religion and economics. It provides innovative solutions to contemporary challenges in the field.